Alterations in salivary biochemical composition and redox state disruption induced by the anticonvulsant valproic acid in male rat salivary glands - de Freitas, Rayara Nogueira [UNESP]; da Silva, Lucas Guilherme Leite [UNESP]; Fiais, Gabriela Alice [UNESP]; Ferreira, Douglas Sandrac de Biagi [UNESP]; Veras, Allice Santos Cruz [UNESP]; Teixeira, Giovana Rampazzo [UNESP]; Oliveira, Sandra Helena Penha [UNESP]; Dornelles, Rita Cássia Menegati [UNESP]; Nakamune, Ana Cláudia de Melo Stevanato [UNESP]; Fakhouri, Walid D.; Chaves-Neto, Antonio Hernandes [UNESP] (Elsevier, 2023)
Objective: To investigate the effects of the anticonvulsant valproic acid (VPA) on salivary glands in male rat using biochemical, functional, histomorphometric, and redox state parameters. Materials and methods: Twenty-four male Wistar rats were randomly distributed into three groups (n = 8 per group): Control (0.9% saline solution), VPA100 (100 mg/kg), and VPA400 (400 mg/kg). After 21 consecutive days of treatment with by intragastric gavage. Pilocarpine-induced saliva was collected to determine salivary flow rate, pH, buffering capacity, and biochemical composition. Analyses of histomorphometric parameters and redox balance markers were performed on the parotid and submandibular glands. Results: Salivary flow rate, pH, buffering capacity, total protein, potassium, sodium, and chloride were similar between groups. However, phosphate and calcium were reduced in VPA400, while amylase was increased in both VPA100 and VPA400. We did not detect significant differences in the areas of acini, ducts, and connective tissue in the salivary glands between the groups. There were no significant changes in the redox status of the submandibular glands. In turn, in the parotid glands we detected reduced total oxidizing capacity and lipid peroxidation, measured as thiobarbituric acid reactive substances (TBARs) and higher uric acid concentration in both the VPA100 and VPA400 groups, and increased superoxide dismutase (SOD) in the VPA400 group. Conclusion: Chronic treatment with VPA modified the salivary biochemical composition and caused disruption in the redox state of the parotid gland in rats.
Keywords: Anticonvulsants; Oxidative stress; Parotid gland; Saliva; Submandibular gland; Valproic acid